2021
DOI: 10.1016/j.pmedr.2021.101353
|View full text |Cite
|
Sign up to set email alerts
|

Associations between depressive symptoms and geriatric syndromes in community-dwelling older adults in Japan: A cross-sectional study

Abstract: Highlights Depressive symptoms are associated with frailty in community-dwelling older adults. AWGS’s new sarcopenia definition is not associated with depressive symptoms. Depressive symptoms may be associated with J-CHS-defined frailty. Among geriatric syndromes, only frailty may be associated with depressive symptoms.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Decreased physical activity [30,31], increased oxidative stress [32,33], increased falling risk, which caused immobility [34,35], malnutrition [4,36], and dysregulated hormonal cycles [37,38] were some of the common risk factors suggested [39] in the literature. While some articles in recent years report the relationship between sarcopenia components and depression [5,[14][15][16][17][18][19][20][21], some of them reported that there is no relationship between sarcopenia components and depression [9][10][11][12][13]. We think there are several points to discuss our results here.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Decreased physical activity [30,31], increased oxidative stress [32,33], increased falling risk, which caused immobility [34,35], malnutrition [4,36], and dysregulated hormonal cycles [37,38] were some of the common risk factors suggested [39] in the literature. While some articles in recent years report the relationship between sarcopenia components and depression [5,[14][15][16][17][18][19][20][21], some of them reported that there is no relationship between sarcopenia components and depression [9][10][11][12][13]. We think there are several points to discuss our results here.…”
Section: Discussionmentioning
confidence: 62%
“…When examining the direct relationship between depression and sarcopenia, these conditions should be excluded. Despite this, many studies have been conducted with depression screening scales and conditions that may cause depressive symptoms have not been excluded [5,[12][13][14][15][16][17][18][19][20][21]. Our preference for strict exclusion criteria while selecting the participants might be the reason why we did not find an independent relationship between sarcopenia components and depression.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Depression is now among the most common diseases in elderly people [9,10]. The study showed that half of the respondents struggle with depressive disorders.…”
Section: Discussionmentioning
confidence: 96%